Neto2-null mice have impaired GABAergic inhibition and are susceptible to seizures - Mahadevan, Vivek; Dargaei, Zahra; Ivakine, Evgueni; Hartmann, Anna-Maria; Ng, David; Chevrier, Jonah; Ormond, John; Nothwang, Hans G.; McInnes, Roderick; Woodin, Melanie A. (Frontiers in Cellular Neuroscience, 2015)
Neto2 is a transmembrane protein that interacts with the neuron-specific K+-Cl- cotransporter (KCC2) in the CNS. Efficient KCC2 transport is essential for setting the neuronal Cl- gradient, which is required for fast GABAergic inhibition. Neto2 is required to maintain the normal abundance of KCC2 in neurons, and increases KCC2 function by binding to the active oligomeric form of this cotransporter. In the present study we characterized GABAergic inhibition and KCC2-mediated neuronal chloride homeostasis in pyramidal neurons from adult hippocampal slices. Using gramicidin perforated patch clamp recordings we found that the reversal potential for GABA (EGABA) was significantly depolarized. We also observed that surface levels of KCC2 and phosphorylation of KCC2 serine 940 (Ser940) were reduced in Neto2-/- neurons compared to wild-type controls. To examine GABAergic inhibition we recorded spontaneous inhibitory postsynaptic currents (sIPSCs) and found that Neto2-/- neurons had significant reductions in both their amplitude and frequency. Based on the critical role of Neto2 in regulating GABAergic inhibition we rationalized that Neto2-null mice would be prone to seizure activity. We found that Neto2-null mice demonstrated a decrease in the latency to pentylenetetrazole (PTZ)-induced seizures and an increase in seizure severity.